Charge Traps in All‐Inorganic CsPbBr3 Perovskite Nanowire Field‐Effect Phototransistors. (6th May 2021) - Winterer, Felix; Walter, Lisa Sophie; Lenz, Jakob; Seebauer, Stefan; Tong, Yu; Polavarapu, Lakshminarayana; Weitz, Ralf Thomas
Abstract: All‐inorganic halide perovskite materials have recently emerged as outstanding materials for optoelectronic applications. However, although critical for developing novel technologies, the influence of charge traps on charge transport in all‐inorganic systems still remains elusive. Here, the charge transport properties in cesium lead bromide, nanowire films are probed using a field‐effect transistor geometry. Field‐effect mobilities of μFET  = 4 × 10 −3  cm −2  V −1  s −1 and photoresponsivities in the range of R  = 25 A W −1 are demonstrated. Furthermore, charge transport both with and without illumination is investigated down to cryogenic temperatures. Without illumination, deep traps dominate transport and the mobility freezes out at low temperatures. Despite the presence of deep traps, when illuminating the sample, the field‐effect mobility increases by several orders of magnitude and even phonon‐limited transport characteristics are visible. This can be seen as an extension to the notion of "defect tolerance" of perovskite materials that has solely been associated with shallow traps. These findings provide further insight in understanding charge transport in perovskite materials and underlines that managing deep traps can open up a route to optimizing optoelectronic devices such as solar cells or phototransistors operable also at low light intensities. Abstract : Why are perovskites so defect tolerant? One answer is provided in the present work using CsPbBr3 nanowire field‐effect transistors. Deep traps, that in dark impede charge transport at low temperatures, do not limit conductivity under illumination and even phonon‐limited transport characteristics become visible in temperature‐dependent mobility measurements.